Applied Designs in Chemical Structures with High Symmetry - JÄNTSCHI, Lorentz; Szefler, Beata (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue, "Applied Designs in Chemical Structures with High Symmetry" is open to submissions and welcomes papers dealing with different orders of symmetry intrinsically present in chemical structures. Characterization of these structures helps broaden our understanding of the natural tendency to stabilize matter into chemical compounds, and pushes us to further develop new classes of highly symmetric chemical compounds. The best example is C60 fullerene (Buckminster fullerene), a purely synthetic form of carbon that was recently found to occur both in nature and outer space, and resembles the balls used in football. Applied designs may simply serve as tools for the in silico construction of chemical structures, as well as for the characterization of a structure, classification of a series of structures, and prediction of their properties (inside of an applicability domain with structure-property relationships).bio